Responding Component in Teacher Noticing and Self-Efficacy of Pre-Service Mathematics Teacher’s Practice - Selfia Putri; Puguh Darmawan; Subanji Subanji (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study investigates how the responding component of teacher noticing and self-efficacy is enacted in the teaching practices of a pre-service mathematics teacher. Using a descriptive qualitative approach with an intrinsic case study design, data were collected through video analysis of teaching practices by pre-service teachers, semi-structured interviews, and teaching documents. Data were analyzed using the interactive model of Miles and Huberman. The results of the analysis show that the responding aspect in teacher noticing is consistently related to the teacher’s self-efficacy dimension. However, the responding is still at the procedural response level and does not reach the student’s thinking analysis that could encourage conceptual understanding abilities. Self-efficacy is relatively strong in student engagement but less evident in instructional strategies and classroom management. These findings provide an integrated understanding of how learning actions emerge from the interplay between teachers’ responding and their self-efficacy, supporting more responsive and student-oriented mathematics learning.